The effect of intracrevicular injection of fucose on serum interlukine -1beta and tumor necrosis factor alpha - Mohammad, Chenar A; Al-Safi , Khlood A; Ahmed, Bakhtiar A (Journal of Baghdad College of Dentistry, 2013)
Background: ?-L-Fucose is a methyl pentose sugar, had the ability to kill bacteria, controlling infection and normalize immune function. The objective of this study is to determine the effect of sulcular injection of fucose on rabbits periodontium , throughout measuring the level of some proinflammatory cytokine ; interlukine 1beta ( IL-1beta) and tumor necrosis factor ( TNF-alpha) in sera of rabbits before fucose injection and at 3 days after fucose injection. Materials and Methods: The study was carried on using ( 20 ) male rabbits of the same species weighted (1-1.5 kg ) , the blood samples were collected from hearts of 20 rabbits before fucose injection and consider as( non injected group) , and after 3 days of fucose injection and consider as (fucose injected group) and analyzed for determination of the concentration of IL-1ß and TNF-?.Results: The results showed a highly significant decrease in the mean concentration of TNF-? in sera of fucose injected group(19.05± 1.166) pg ?ml when compared to its mean concentration in non injected group (27.25±7.371) pg ?ml ,also a highly significant decrease in the mean concentration of IL-1ß in sera of fucose injected group(34.19 ± 3.1)pg ?ml as compared to its mean concentration in sera of non injected group (38.86 ±4.565)pg?ml. Conclusion: both proinflammatory cytokines were influenced and inhibited by local fucose injection